2010
DOI: 10.1007/s00262-010-0925-y
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to the proapoptotic effects of interferon-gamma on melanoma cells used in patient-specific dendritic cell immunotherapy is associated with improved overall survival

Abstract: The use of whole cell tumor vaccines and various means of loading antigen onto dendritic cells have been under investigation for over a decade. Induction of apoptosis and the exposure of immune-stimulating proteins are thought to be beneficial for the use in immunotherapy protocols, but conclusive evidence in the clinical setting has been lacking. Incubation of melanoma cell lines with interferon-gamma (IFN-γ) increased phosphatidylserine and calreticulin exposure, but not in the IFN-γ-resistant cell line Lu-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…The resulting presence of apoptotic cells after IFN-c treatment was associated with significant decreases in progression-free and overall survival, which was reported elsewhere. 20 In agreement with this published report, a log-rank test revealed a significant association with lower viability upon IFN-c treatment of melanoma tumor cells and overall survival in patients under study (data not shown).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The resulting presence of apoptotic cells after IFN-c treatment was associated with significant decreases in progression-free and overall survival, which was reported elsewhere. 20 In agreement with this published report, a log-rank test revealed a significant association with lower viability upon IFN-c treatment of melanoma tumor cells and overall survival in patients under study (data not shown).…”
Section: Resultssupporting
confidence: 91%
“…31 However, recent published data demonstrated that a resistance to the proapoptotic effects of IFN-c was associated with a better clinical outcome. 20 Although IL-12 secretion by mature DCs can lead to robust CTL activity, there has been some controversy as to whether ex vivo maturation leads to lasting tumor immunity. 32 The risk of induction of regulatory T cells, which can suppress antigen-specific CTLs, by immature DCs has also been shown to occur with cytokine-matured DCs.…”
Section: Discussionmentioning
confidence: 99%
“…By enhancing immunogenicity, also CRT correlates with favorable prognosis for patients with, for example, lung cancer [39], gastric cancer [40], and leukemia [41]. CRT on melanoma cells was also involved in dendritic cell vaccination in melanoma patients, although cell death was found to be dispensable for that effect [42]. Exogenously added CRT also potentiates the immunogenicity of melanomas in patients [43].…”
Section: Discussionmentioning
confidence: 99%
“…8,15 However, univariate and multivariate analyses failed to show a correlation between such expression and efficacy, 16 so for this trial, the TCs were not exposed to IFN-g. TCs were irradiated with 10 Gy in a cesium irradiator to induce apotosis, then aliquoted and cryopreserved for therapeutic use. The resulting cell suspension was either cryopreserved and later put into culture, or directly placed in culture in flasks containing enriched Rosewell Park Memorial Institute-1640 culture media.…”
Section: Autologous Tc Vaccinementioning
confidence: 81%